MEWUJUDKAN SEKOLAH YANG ADAPTIF,INOVATIF DAN UNGGUL DALAM ERA SOCIETY 5.0 DI JENJANG SEKOLAH DASAR - Wirma Datil Husna , Nurtika Syafitri , Herlina Saswita , Nurhayati , Irma Yendi; Dewi Oktavia , Weni Yulastri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of information and communication technology in the Society 5.0 Era demands that educational institutions, including elementary schools, transform into adaptive, innovative, and excellent institutions. Elementary schools hold a strategic role in preparing a generation that is not only knowledgeable but also possesses strong character, digital literacy, and 21st-century skills. This study aims to analyze the concepts, strategies, and challenges faced by elementary schools in realizing adaptive, innovative, and excellent educational institutions in the Society 5.0 Era. The method used is a literature review by examining various relevant academic literatures from the past ten years. The results of the study indicate that adaptive schools are characterized by the institution's ability to respond to social dynamics and technological developments through flexible management policies, digital-based curricula, and technology-based learning. Innovation in elementary schools becomes the key to improving the quality of educational services, including the development of digital learning methods, ICT-based student services, and strengthening character education. Excellent schools are measured not only through academic achievements but also by students' digital competence, character, and the transformative leadership of school principals. This transformation requires collaborative support from parents, the community, and strategic partnerships among educational stakeholders.